2012
DOI: 10.1128/iai.06354-11
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Meningococcal PilU Delays Microcolony Formation and Attenuates Virulence In Vivo

Abstract: ABSTRACTNeisseria meningitidisis a major cause of sepsis and bacterial meningitis worldwide. This bacterium expresses type IV pili (Tfp), which mediate important virulence traits such as the formation of bacterial aggregates, host cell adhesion, twitching motility, and DNA uptake. The meningococcal PilT protein is a hexameric ATPase that mediates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
(42 reference statements)
3
22
0
Order By: Relevance
“…In this study, we investigated the importance of epithelial cells and cell-derived factors for microcolony dispersal. We demonstrated that the previously observed short and synchronized dispersal of microcolonies [41] requires the presence of live epithelial cells but not direct contact between cells and bacteria. Microcolony dispersal could be induced by a low-molecular weight host cell-derived factor that accumulated in cell-conditioned medium (i.e., CM) in absence of infectious agent.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, we investigated the importance of epithelial cells and cell-derived factors for microcolony dispersal. We demonstrated that the previously observed short and synchronized dispersal of microcolonies [41] requires the presence of live epithelial cells but not direct contact between cells and bacteria. Microcolony dispersal could be induced by a low-molecular weight host cell-derived factor that accumulated in cell-conditioned medium (i.e., CM) in absence of infectious agent.…”
Section: Discussionmentioning
confidence: 67%
“…While this shows that PNPase is required for full virulence in this mouse model, the mechanism for decreased bacterial survival is unclear. Previous studies of bacteremia that used the hyperaggregative nafA-and pilT-deficient N. meningitidis mutants showed that these mutants also displayed decreased survival (39,64). We cannot exclude the possibility that the decreased bacterial counts in blood were due to an increase in bacterial binding to host cells as a result of excessive aggregation.…”
Section: Discussionmentioning
confidence: 68%
“…PilU was long speculated to play a role in Tfp retraction due its co‐transcription with and structural similarity to PilT. Ngo and Neisseria meningitidis mutants deleted of pilU show differences in microcolony formation and infection dynamics compared to wt, further implicating a role for PilU in Tfp retraction (Park et al ., ; Eriksson et al ., ). Our findings lend support to this idea.…”
Section: Discussionmentioning
confidence: 87%